# Solve the following equation: ${x^4} + 1 - 3\left( {{x^3} + x} \right) = 2{x^2}$.

Answer

Verified

368.1k+ views

Hint: Here, we will proceed by replacing $x$ by $\dfrac{1}{x}$in the given equation in order to prove that it will come out as the same.

Given, equation is ${x^4} + 1 - 3\left( {{x^3} + x} \right) = 2{x^2} \Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0{\text{ }} \to {\text{(1)}}$

Let us replace $x$ by $\dfrac{1}{x}$ in equation (1), we get

$

\Rightarrow {\left( {\dfrac{1}{x}} \right)^4} - 3{\left( {\dfrac{1}{x}} \right)^3} - 2{\left( {\dfrac{1}{x}} \right)^2} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{1}{{{x^4}}} - \dfrac{3}{{{x^3}}} - \dfrac{2}{{{x^2}}} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{{1 - 3x - 2{x^2} - 3{x^3} + {x^4}}}{{{x^4}}} = 0 \\

\Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0 \\

$

Clearly, the above equation which is obtained by replacing $x$ by $\dfrac{1}{x}$in the given equation (1) is the same as the given equation (1).

As, we know that when in a polynomial of degree four (having two roots as $\alpha $ and $\beta $ ) if $x$ is replaced by $\dfrac{1}{x}$ and the polynomial comes out to be same as previous one then the other two roots of that polynomial will be $\dfrac{1}{\alpha }$ and $\dfrac{1}{\beta }$.

Also, for any general polynomial of degree four \[a{x^4} + b{x^3} + c{x^2} + dx + e = 0\]

\[

{\text{Sum of all the roots}} = - \dfrac{b}{a} \\

{\text{Sum of product of different roots taken two at a time }} = \dfrac{c}{a} \\

\]

According to the given equation (1), we can say \[a = 1\],\[b = - 3\],\[c = - 2\],\[d = - 3\]and \[e = 1\].

Therefore, Sum of all the roots of the given equation (1) is given by \[\alpha + \beta + \dfrac{1}{\alpha } + \dfrac{1}{\beta } = - \dfrac{{\left( { - 3} \right)}}{1} = 3{\text{ }} \to {\text{(2)}}\]

Sum of product of different roots taken two at a time of the given equation (1) is given by

\[

\alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\beta {\text{.}}\dfrac{1}{\beta }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{{\left( { - 2} \right)}}{1} = - 2 \\

\Rightarrow \alpha \beta {\text{ + }}1{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}1{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = - 2 \Rightarrow \alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta } = - 2 - 2 = - 4 \\

\]

\[ \Rightarrow \alpha \left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right){\text{ + }}\dfrac{1}{\alpha }\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4 \Rightarrow \left( {\alpha + \dfrac{1}{\alpha }} \right)\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4{\text{ }} \to {\text{(3)}}\]

Now, equation (2) can be re-arranged as \[\left( {\alpha + \dfrac{1}{\alpha }} \right) = 3 - \left( {\beta + \dfrac{1}{\beta }} \right)\]

Put the value of \[\left( {\alpha + \dfrac{1}{\alpha }} \right){\text{ }}\]in equation (3), we get

\[\left[ {3 - \left( {\beta + \dfrac{1}{\beta }} \right)} \right]\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4\]

Let \[\left( {\beta + \dfrac{1}{\beta }} \right) = t\]

\[

\Rightarrow \left[ {3 - t} \right]t = - 4 \Rightarrow {t^2} - 3t - 4 = 0 \Rightarrow {t^2} + t - 4t - 4 = 0 \Rightarrow t\left( {t + 1} \right) - 4\left( {t + 1} \right) = 0 \\

\Rightarrow \left( {t + 1} \right)\left( {t - 4} \right) = 0 \\

\]

\[ \Rightarrow t = - 1\] or \[t = 4\]

\[\beta + \dfrac{1}{\beta } = - 1 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = - 1 \Rightarrow {\beta ^2} + \beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( 1 \right) \pm \sqrt {{{\left( 1 \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{ - 1 \pm \sqrt {1 - 4} }}{2} = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\] or \[\beta + \dfrac{1}{\beta } = 4 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = 4 \Rightarrow {\beta ^2} - 4\beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( { - 4} \right) \pm \sqrt {{{\left( { - 4} \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{4 \pm \sqrt {16 - 4} }}{2} = \dfrac{{4 \pm 2\sqrt 3 }}{2} = 2 \pm \sqrt 3 \]

Hence, \[\beta = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]or \[\beta = 2 \pm \sqrt 3 \]

Using equation (2) put the value of \[\beta \], we will get the value for \[\alpha \]

\[\alpha = 2 \pm \sqrt 3 \]or \[\alpha = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]

Therefore, all the roots of the given are \[2 \pm \sqrt 3 \], \[\dfrac{{ - 1 \pm i\sqrt 3 }}{2}\].

Note: These types of problems are solved by somehow checking for some properties regarding roots of a polynomial and then finding out an appropriate relation between the roots and hence solving further to get them.

Given, equation is ${x^4} + 1 - 3\left( {{x^3} + x} \right) = 2{x^2} \Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0{\text{ }} \to {\text{(1)}}$

Let us replace $x$ by $\dfrac{1}{x}$ in equation (1), we get

$

\Rightarrow {\left( {\dfrac{1}{x}} \right)^4} - 3{\left( {\dfrac{1}{x}} \right)^3} - 2{\left( {\dfrac{1}{x}} \right)^2} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{1}{{{x^4}}} - \dfrac{3}{{{x^3}}} - \dfrac{2}{{{x^2}}} - \dfrac{3}{x} + 1 = 0{\text{ }} \Rightarrow \dfrac{{1 - 3x - 2{x^2} - 3{x^3} + {x^4}}}{{{x^4}}} = 0 \\

\Rightarrow {x^4} - 3{x^3} - 2{x^2} - 3x + 1 = 0 \\

$

Clearly, the above equation which is obtained by replacing $x$ by $\dfrac{1}{x}$in the given equation (1) is the same as the given equation (1).

As, we know that when in a polynomial of degree four (having two roots as $\alpha $ and $\beta $ ) if $x$ is replaced by $\dfrac{1}{x}$ and the polynomial comes out to be same as previous one then the other two roots of that polynomial will be $\dfrac{1}{\alpha }$ and $\dfrac{1}{\beta }$.

Also, for any general polynomial of degree four \[a{x^4} + b{x^3} + c{x^2} + dx + e = 0\]

\[

{\text{Sum of all the roots}} = - \dfrac{b}{a} \\

{\text{Sum of product of different roots taken two at a time }} = \dfrac{c}{a} \\

\]

According to the given equation (1), we can say \[a = 1\],\[b = - 3\],\[c = - 2\],\[d = - 3\]and \[e = 1\].

Therefore, Sum of all the roots of the given equation (1) is given by \[\alpha + \beta + \dfrac{1}{\alpha } + \dfrac{1}{\beta } = - \dfrac{{\left( { - 3} \right)}}{1} = 3{\text{ }} \to {\text{(2)}}\]

Sum of product of different roots taken two at a time of the given equation (1) is given by

\[

\alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\beta {\text{.}}\dfrac{1}{\beta }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = \dfrac{{\left( { - 2} \right)}}{1} = - 2 \\

\Rightarrow \alpha \beta {\text{ + }}1{\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}1{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta }{\text{ }} = - 2 \Rightarrow \alpha \beta {\text{ + }}\alpha {\text{.}}\dfrac{1}{\beta }{\text{ + }}\beta {\text{.}}\dfrac{1}{\alpha }{\text{ + }}\dfrac{1}{\alpha }{\text{.}}\dfrac{1}{\beta } = - 2 - 2 = - 4 \\

\]

\[ \Rightarrow \alpha \left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right){\text{ + }}\dfrac{1}{\alpha }\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4 \Rightarrow \left( {\alpha + \dfrac{1}{\alpha }} \right)\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4{\text{ }} \to {\text{(3)}}\]

Now, equation (2) can be re-arranged as \[\left( {\alpha + \dfrac{1}{\alpha }} \right) = 3 - \left( {\beta + \dfrac{1}{\beta }} \right)\]

Put the value of \[\left( {\alpha + \dfrac{1}{\alpha }} \right){\text{ }}\]in equation (3), we get

\[\left[ {3 - \left( {\beta + \dfrac{1}{\beta }} \right)} \right]\left( {\beta {\text{ + }}\dfrac{1}{\beta }} \right) = - 4\]

Let \[\left( {\beta + \dfrac{1}{\beta }} \right) = t\]

\[

\Rightarrow \left[ {3 - t} \right]t = - 4 \Rightarrow {t^2} - 3t - 4 = 0 \Rightarrow {t^2} + t - 4t - 4 = 0 \Rightarrow t\left( {t + 1} \right) - 4\left( {t + 1} \right) = 0 \\

\Rightarrow \left( {t + 1} \right)\left( {t - 4} \right) = 0 \\

\]

\[ \Rightarrow t = - 1\] or \[t = 4\]

\[\beta + \dfrac{1}{\beta } = - 1 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = - 1 \Rightarrow {\beta ^2} + \beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( 1 \right) \pm \sqrt {{{\left( 1 \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{ - 1 \pm \sqrt {1 - 4} }}{2} = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\] or \[\beta + \dfrac{1}{\beta } = 4 \Rightarrow \dfrac{{{\beta ^2} + 1}}{\beta } = 4 \Rightarrow {\beta ^2} - 4\beta + 1 = 0 \Rightarrow \beta = \dfrac{{ - \left( { - 4} \right) \pm \sqrt {{{\left( { - 4} \right)}^2} - 4 \times 1 \times 1} }}{{2 \times 1}} = \dfrac{{4 \pm \sqrt {16 - 4} }}{2} = \dfrac{{4 \pm 2\sqrt 3 }}{2} = 2 \pm \sqrt 3 \]

Hence, \[\beta = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]or \[\beta = 2 \pm \sqrt 3 \]

Using equation (2) put the value of \[\beta \], we will get the value for \[\alpha \]

\[\alpha = 2 \pm \sqrt 3 \]or \[\alpha = \dfrac{{ - 1 \pm i\sqrt 3 }}{2}\]

Therefore, all the roots of the given are \[2 \pm \sqrt 3 \], \[\dfrac{{ - 1 \pm i\sqrt 3 }}{2}\].

Note: These types of problems are solved by somehow checking for some properties regarding roots of a polynomial and then finding out an appropriate relation between the roots and hence solving further to get them.

Last updated date: 27th Sep 2023

â€¢

Total views: 368.1k

â€¢

Views today: 9.68k

Recently Updated Pages

What do you mean by public facilities

Difference between hardware and software

Disadvantages of Advertising

10 Advantages and Disadvantages of Plastic

What do you mean by Endemic Species

What is the Botanical Name of Dog , Cat , Turmeric , Mushroom , Palm

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is meant by shramdaan AVoluntary contribution class 11 social science CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

An alternating current can be produced by A a transformer class 12 physics CBSE

What is the value of 01+23+45+67++1617+1819+20 class 11 maths CBSE

Give 10 examples for herbs , shrubs , climbers , creepers